2015
DOI: 10.1371/journal.pone.0145823
|View full text |Cite
|
Sign up to set email alerts
|

Co-Carriage of blaKPC-2 and blaNDM-1 in Clinical Isolates of Pseudomonas aeruginosa Associated with Hospital Infections from India

Abstract: Global spread of KPC poses to be a serious threat complicating treatment options in hospital settings. The present study investigates the genetic environment of bla KPC-2 among clinical isolates of Pseudomonas aeruginosa from a tertiary referral hospital of India. The study isolates were collected from different wards and clinics of Silchar Medical College and Hospital, India, from 2012–2013. The presence of bla KPC was confirmed by genotypic characterization followed by sequencing. Cloning of the bla KPC-2 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…bla VIM + bla NDM-1 was the most common combination (6/102, 5.88%), followed by bla VIM + bla GIM (3/102, 2.94%). The coproduction of bla VIM + bla NDM-1 had previously been described in 7.1% CRPA isolates by Ellapan et al [15] The coexistence of bla VIM + bla NDM-1 and bla KPC-2 and bla NDM-1 in CRPA isolates from India is also described previously by Paul et al [18,19] No carbapenem-resistant gene was detected in 38 (38/102, 37.25%) CRPA isolates in our study. Other carbapenem mechanisms such as efflux pump and porin loss could have contributed for carbapenemase resistance, which were not studied in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…bla VIM + bla NDM-1 was the most common combination (6/102, 5.88%), followed by bla VIM + bla GIM (3/102, 2.94%). The coproduction of bla VIM + bla NDM-1 had previously been described in 7.1% CRPA isolates by Ellapan et al [15] The coexistence of bla VIM + bla NDM-1 and bla KPC-2 and bla NDM-1 in CRPA isolates from India is also described previously by Paul et al [18,19] No carbapenem-resistant gene was detected in 38 (38/102, 37.25%) CRPA isolates in our study. Other carbapenem mechanisms such as efflux pump and porin loss could have contributed for carbapenemase resistance, which were not studied in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, a report from India also has established its chromosomal location [ 19 ]. However, in our recent study we found presence of bla NDM-1 on plasmid DNA indicating a possible shift from one to another genetic location [ 20 ]. Future experiments will show which direction (chromosome to plasmid or vice versa) of the transfer took place in the organism.…”
Section: Discussionmentioning
confidence: 99%
“…After overnight incubation, plasmids were extracted by QIAprep Spin Miniprep Kit (Qiagen, Germany). Plasmids of bla NDM-1 were subjected to transformation by heat shock method10 using Escherichia coli JM107 as recipient. Transformants were selected on LB agar with 0.25 μg/ml of imipenem, which were then confirmed both by phenotypic as well as by PCR analysis.…”
mentioning
confidence: 99%
“…A total of 18 different replicon types such as FIA, FIB, FIC, HI1, HI2, I1/Iγ, L/M, N, P, W, T, A/C, K, B/O, X, Y, F and FIIA were targeted as described previously11. The antibiotic susceptibility was done by Kirby-Bauer disc-diffusion method10 against antibiotics viz . piperacillin-tazobactam (100/10 μg), co-trimoxazole (25 μg), amikacin (30 μg), gentamicin (10 μg), ciprofloxacin (5 μg), polymixin B (300 units), netilmicin (30 μg), carbenicillin (100 μg) and faropenem (5 μg) (Hi-Media, Mumbai, India).…”
mentioning
confidence: 99%